Tumour Calcification and Calciphylaxis in End-Stage Renal Disease - Jia Di; Zhenxing Jiang; Min Yang (Case Reports in Medicine)
Although soft tissue and vascular calcifications are common in CKD and progress as an independent risk factor of all-cause mortality, tumour calcification and calciphylaxis are uncommon in patients with end-stage renal disease (ESRD). Here, we discuss a rare case of a patient with tumour calcification complicated with calciphylaxis developed septic shock from infection. Our patient is a 57-year-old man in his late stage of renal disease who presented with a huge mass at the right hip and necrotic cutaneous ulcers on the lower legs followed by local and systemic infection and death due to septic shock.